Ultrastable metal oxide nanotube arrays achieved by entropy-stabilization engineering. (15th March 2018) - Lei, Zhifeng; Liu, Xiongjun; Li, Rui; Wang, Hui; Wu, Yuan; Lu, Zhaoping
Abstract: Metal oxide nanotube arrays have recently attracted extensive attention due to their widespread use in the field of catalysis and energy storage. However, the low structural stability of the currently available nanotube arrays severely limits their efficiency and high-temperature applications. By applying the entropy-stabilization engineering strategy, we developed ultrastable metal oxide nanotube arrays consisting of multiple oxide constituents by anodic oxidation of high-entropy alloy precursors, which can sustain 800 °C heat-treatment without crystallization and resist 1000 °C calcination without collapse. The superior thermal stability endows the high-entropy oxide nanotube arrays a promising candidate for high-temperature applications. Graphical abstract: Image 1